Evaluasi Kinerja SATPOL PP dalam Menerapkan Ketertiban Umum pada Kawasan Pedagang Kaki Lima di Pasar Puan Maimun Kecamatan Karimun - Nurma Lingga Wati; Rumzi Samin; Okparizan Okparizan (Lembaga Pengembangan Kinerja Dosen, 2023)
The implementation of public order for street vendors (PKL) is still a problem, due to the lack of handling carried out by the local government, causing the community to deliberately violate the trading place. The background of this research is to find out the obstacles in carrying out the duties of the civil service police unit in the Karimun sub-district in controlling street vendors. The method used in this research is to use a qualitative descriptive approach with data sources in observation, interviews, and documentation. The theory used in this study is the theory of the four main elements of performance evaluation measurement according to Mahsum (2013: 26) namely (1) the goals and objectives carried out by SATPOL PP have been carried out in accordance with established regional regulations even though there are several street vendors in the Puan market Maimun who has not optimally understood the regulations from SATPOL PP. (2) the performance measurement of SATPOL PP as public control can be said to be quite effective even though not as a whole in socializing the ban on selling on public roads. (3) in measuring the level of achievement of SATPOL PP targets, it can be said that the level of achievement is in the category of success in providing solutions related to selling on the roadside, it's just that there is a lack of strategy in spatial planning. (4) in evaluating the performance of SATPOL PP it has been optimal but there is still a lack of routine supervision and maximum sanctions, this is due to the lack of firm attitude and commitment from officers who violate the rules so that the handling of street vendors is not optimal. The conclusion of this study is that the Karimun Regency SATPOL PP has carried out public control of street vendors at the Puan Maimun market in accordance with regional regulation No. 1 of 2019 concerning public order. suggestions that SATPOL PP should provide regular outreach regarding the orderly regulations for street vendors, supervise officers who are undisciplined, give directions evenly and stipulate strict sanctions against street vendors who violate the rules.